Nitrogen oxides emissions from the MILD combustion with the conditions of recirculation gas. (3rd April 2017) - Park, Min; Shim, Sung Hoon; Jeong, Sang Hyun; Oh, Kwang-Joong; Lee, Sang-Sup
ABSTRACT: The nitrogen oxides (NOx ) reduction technology by combustion modification which has economic benefits as a method of controlling NOx emitted in the combustion process, has recently been receiving a lot of attention. Especially, the moderate or intense low oxygen dilution (MILD) combustion which applied high temperature flue gas recirculation has been confirmed for its effectiveness with regard to solid fuel as well. MILD combustion is affected by the flue gas recirculation ratio and the composition of recirculation gas, so its NOx reduction efficiency is determined by them. In order to investigate the influence of factors which determine the reduction efficiency of NOx in MILD coal combustion, this study changed the flow rate and concentration of nitrogen (N2 ), carbon dioxide (CO2 ) and steam (H2 O) which simulate the recirculation gas during the MILD coal combustion using our lab-scale drop tube furnace and performed the combustion experiment. As a result, its influence by the composition of recirculation gas was insignificant and it was shown that flue gas recirculation ratio influences the change of NOx concentration greatly. Implications : We investigated the influence of factors determining the nitrogen oxides (NOx ) reduction efficiency in MILD coal combustion, which applied high-temperature flue gas recirculation. Using a lab-scale drop tube furnace and simulated recirculation gas, we conducted combustion testing changing the recirculation gas conditions. We found that the flue gas recirculation ratio influences the reduction of NOx emissions the most.